Integrated plug flow synthesis and crystallisation of pyrazinamide. Issue 5 (25th July 2018) - Scott, C. Daniel; Labes, Ricardo; Depardieu, Martin; Battilocchio, Claudio; Davidson, Matthew G.; Ley, Steven V.; Wilson, Chick C.; Robertson, Karen
Abstract : Pure pyrazinamide has been produced in a coupled flow synthesis and crystallisation in high yield, pure polymorphic form (γ) and narrow particle size distribution. Abstract : We report the integration of flow chemistry with plug flow crystallisation. Catalytic flow hydration of pyrazinecarbonitrile to pyrazinamide was performed in a packed bed column of MnO2 . The effluent of this flow reactor was directly linked to a tri-segmented tubular crystalliser (KRAIC), providing a seamless transition from flow synthesis to crystallisation, with control over solid form and particle characteristics.